2012
DOI: 10.1111/1365-2656.12021
|View full text |Cite
|
Sign up to set email alerts
|

Female ornaments revisited – are they correlated with offspring quality?

Abstract: Summary1. The evolution and signalling content of female ornamentation has remained an enduring challenge to evolutionary biologists, despite the fact that secondary sexual characters are widespread in females. While females usually invest significant amounts of their resources, including carotenoids, in offspring, all the resources allocated to elaborate ornamentation reduce resources available for other purposes. This may in turn constrain female fitness leading to dishonest female signalling. 2. We review t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
63
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 62 publications
(64 citation statements)
references
References 105 publications
(86 reference statements)
1
63
0
Order By: Relevance
“…Previous studies in tree swallows also have shown that more ornamented females have greater levels of nest parasitism, poorer immune defences, lower hematocrit levels and produce offspring that are smaller or in poor condition (Coady, 2011;Bentz and Siefferman, 2013). This negative relationship between female ornamentation and offspring quality could be interpreted as evidence in support of the genetic correlation hypothesis (Nordeide et al, 2013); however, more ornamented female tree swallows may experience social costs as a result of conspecifics challenging their status (Coady, 2011;Chapter 3), thereby resulting in poorer quality offspring produced by more ornamented females.…”
Section: Introductionmentioning
confidence: 66%
See 4 more Smart Citations
“…Previous studies in tree swallows also have shown that more ornamented females have greater levels of nest parasitism, poorer immune defences, lower hematocrit levels and produce offspring that are smaller or in poor condition (Coady, 2011;Bentz and Siefferman, 2013). This negative relationship between female ornamentation and offspring quality could be interpreted as evidence in support of the genetic correlation hypothesis (Nordeide et al, 2013); however, more ornamented female tree swallows may experience social costs as a result of conspecifics challenging their status (Coady, 2011;Chapter 3), thereby resulting in poorer quality offspring produced by more ornamented females.…”
Section: Introductionmentioning
confidence: 66%
“…In contrast, traits that appear to not be preferred by males or reflect female quality, or are negatively related to offspring quality (e.g., Muma and Weatherhead, 1989;Cuervo et al, 1996;Wolf et al, 2004; reviewed in Nordeide et al, 2013), are hypothesized to evolve as a by-product of selection acting on ornamentation displayed by males (i.e., genetic correlation hypothesis, Lande, 1980). The focus of studies on male mate choice, however, may be too narrow to fully understand the evolution of ornamentation in females (Tarvin and Murphy, 2012), especially since ornamental traits, such as aggressive behaviour, may enable females to outcompete conspecifics (Rosvall, 2008), but entail costs to offspring quality (Rosvall, 2011b).…”
Section: Function and Evolution Of Ornamental Traits Of Femalesmentioning
confidence: 99%
See 3 more Smart Citations